Favorable outcomes of prepackaged low‐residue diet on bowel preparation for colonoscopy: Endoscopist‐blinded randomized controlled trial. Issue 5 (24th October 2018) - Lee, Jung Won; Choi, Joon Young; Yoon, Hyuk; Shin, Cheol Min; Park, Young Soo; Kim, Nayoung; Lee, Dong Ho
Abstract: Background and Aim: 2 L polyethylene glycol plus an ascorbic acid (PEGA) is known to be as effective. However, 2 L polyethylene glycol‐based regimens are often still difficult for patients to tolerate. Therefore, we conducted this study to evaluate the potential of 1 L PEGA with prepackaged low‐residue diet (PLD) as an alternative to 2 L PEGA before colonoscopy. Methods: The subjects were randomly assigned to either of the two groups. The 2 L PEGA group received 2 L PEGA split regimen. The 1 L PEGA with PLD group received PLD on the day preceding colonoscopy and 1 L PEGA. All endoscopic procedures were performed by one physician who did not know patients allocation. Bowel preparation status were graded using Boston Bowel Preparation Score (BBPS). A questionnaire regarding tolerability and safety was administered. This trial is registered at ClinicalTrials.gov (NCT03329339). Results: A total of 173 patients completed the study (86 in the 2 L PEGA group and 87 in the 1 L PEGA with PLD group). Bowel preparation was adequate in 88.4% (76/86) of patients in the 2 L PEGA group and 93.1% of patients in the 1 L PEGA with PLD group (81/87, P  = 0.28). The patients in the 1 L PEGA with PLD group had higher whole Boston Bowel Preparation Scale score ( P  = 0.02) and expressed more satisfaction and willingness to repeat the procedure ( P  < 0.01). There was no significant difference with respect to compliance or safety. Conclusion: 1 L PEGA with PLD showed equivalent efficacy, greater satisfaction, and more willingness to repeat compared with 2 L PEGA for bowel preparation.